Anesthesia Exposure and Risk of Dementia and Alzheimer's Disease: A Prospective Study. Issue 3 (11th February 2016) - Aiello Bowles, Erin J.; Larson, Eric B.; Pong, Ryan P.; Walker, Rod L.; Anderson, Melissa L.; Yu, Onchee; Gray, Shelly L.; Crane, Paul K.; Dublin, Sascha
Abstract : Objectives: To evaluate the associations between anesthesia and dementia or Alzheimer's disease (AD) risk using prospectively collected data. Design: Cohort study. Participants: Community‐dwelling members of the Adult Changes in Thought cohort aged 65 and older and free of dementia at baseline (N = 3, 988). Measurements: Participants self‐reported all prior surgical procedures with general or neuraxial (spinal or epidural) anesthesia at baseline and reported new procedures every 2 years. People undergoing high‐risk surgery with general anesthesia, other surgery with general anesthesia, and other surgery with neuraxial anesthesia exposures were compared with those with no surgery and no anesthesia. Cox proportional hazards models were used to estimate hazard ratios (HRs) and 95% confidence intervals (CIs) for dementia and AD associated with time‐varying lifetime and recent (past 5 years) anesthesia exposures. Results: At baseline, 254 (6%) people reported never having anesthesia; 248 (6%) had had one or more high‐risk surgeries with general anesthesia, 3, 363 (84%) had had one or more other surgeries with general anesthesia, and 123 (3%) had had one or more surgeries with neuraxial anesthesia. High‐risk surgery with general anesthesia was not associated with greater risk of dementia (HR = 0.86, 95% CI = 0.58–1.28) or AD (HR = 0.95, 95% CI = 0.61–1.49) than no history of anesthesia. People with any history of other surgery with general anesthesia had a lower risk of dementia (HR = 0.63, 95% CI = 0.46–0.85) and AD (HR = 0.65, 95% CI = 0.46–0.93) than people with no history of anesthesia. There was no association between recent anesthesia exposure and dementia or AD. Conclusion: Anesthesia exposure was not associated with of dementia or AD in older adults.